Kedudukan Dan Kewenangan Wakil Presiden Dan Platform Lapor! Mas Wapres: Analisis Dalam Konteks Demokrasi Digital - Putri Cahyani, Selvi (Sultra Research of Law, 2025)
The digital transformation of governance has driven public service innovations, including the LAPOR! Mas Wapres platform initiated by the Vice President of the Republic of Indonesia. This initiative raises controversy due to the absence of explicit constitutional provisions regarding the Vice President’s administrative authority. This study normatively analyzes the legal status and limitations of the Vice President’s authority in managing digital-based public administration, as well as its implications for digital democracy and good governance. It employs a normative qualitative approach with library research and descriptive-analytical techniques. The results indicate that the Vice President lacks autonomous administrative authority unless explicitly delegated by the President. Therefore, any management of public digital platforms by the Vice President must be supported by formal legal regulation to avoid authority overlap and legitimacy issues. The study recommends establishing clear regulations and institutional integration to enhance accountability and strengthen digital democracy in Indonesia.